A revision of the Ewartia oldfieldi (Distant) species complex (Hemiptera: Cicadidae: Cicadettinae) with five new species from eastern and northern Australia - Popple, Lindsay W. (Zootaxa, 2017)
The identity of Ewartia oldfieldi (Distant) is re-examined and this species is redescribed. Five new species belonging to the genus Ewartia Moulds are described. Ewartia oldfieldi s. str. occurs in association with wattles (Acacia spp.; Mimosaceae) with large or fleshy phyllodes growing in soils derived from sandstone and coarse-grained metasediments throughout the south-eastern third of Queensland. Ewartia roberti n. sp. is associated with wattles that possess narrow or delicate phyllodes, growing in loam soils in southern Queensland and northern New South Wales. Ewartia lapidosa n. sp. occurs in dryer inland and semi-arid areas between Croydon in northern Queensland and the Capertee Valley in central New South Wales where it occurs on various wattles growing in hard, rocky soils, including those derived from laterite and sandstone. Ewartia etesia n. sp. occurs principally on wattles growing along drainage lines in the Top End of the Northern Territory and the eastern edge of the Kimberley in Western Australia. Ewartia thamna n. sp. occurs in low, shrubby vegetation (presumably on wattles) in gravelly soils on low rises and along floodplains at the southern edge of the Top End in the Northern Territory. Ewartia carina n. sp. occurs in transitional habitats with tropical rainforest elements on the eastern edge of Cape York Peninsula in north Queensland. The distinctive, sometimes variable and typically complex calling songs specific to each of the species are illustrated and documented as part of these descriptions and comparisons.